2008
DOI: 10.1155/2008/385108
|View full text |Cite
|
Sign up to set email alerts
|

C‐Peptide and Atherogenesis: C‐Peptide as a Mediator of Lesion Development in Patients with Type 2 Diabetes Mellitus?

Abstract: Patients with insulin resistance and early type 2 diabetes exhibit an increased propensity to develop a diffuse and extensive pattern of arteriosclerosis. Typically, these patients show increased levels of C-peptide and over the last years various groups examined the effect of C-peptide in vascular cells as well as its potential role in lesion development. While some studies demonstrated beneficial effects of C-peptide, for example, by showing an inhibition of smooth muscle cell proliferation, others suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…Multivariable analyses to determine the effect of elevated C-peptide (T 3 ) compared to its normal values (terciles 1 plus 2) in the population with blood glucose < 126 mg/dL (n = 5673) consistently showed a significant effect of T 3 …”
Section: Resultsmentioning
confidence: 99%
“…Multivariable analyses to determine the effect of elevated C-peptide (T 3 ) compared to its normal values (terciles 1 plus 2) in the population with blood glucose < 126 mg/dL (n = 5673) consistently showed a significant effect of T 3 …”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have found cross-sectional associations between low C-peptide levels and either microvascular or macrovascular complications and cardiovascular risk factors in type 2 diabetes (15,16,17), and most experiments with C-peptide supplementation have promoted vascular lesions and insulin resistance (24,25). In type 2 diabetes, elevations in C-peptide levels are usually observed as a consequence of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the beneficial effects of C-peptide on vessels by inhibiting smooth muscle cell proliferation and migration and antiinflammatory activity in endothelial cells (2,27,28). Other studies have revealed C-peptide deposition in the arteriosclerotic lesions of diabetic patients, chemotactic activity towards monocytes and CD4C lymphocytes and the induction of vascular smooth muscle cell proliferation (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The internalisation of C-peptide was explored in human aortic endothelial cells (HAEC) and umbilical artery smooth muscle cells (UASMC), two important targets of C-peptide activity, especially in the context of vascular dysfunction leading to vascular complications in type 1 diabetes [13][14][15][16]. We found that in these cells C-peptide internalises from the cellular surface within punctate structures, most of them co-localizing with early endosomes.…”
Section: Introductionmentioning
confidence: 99%